Pengaruh penambahan sari temulawak (Curcuma xanthorrhiza) terhadap total fenol, kadar garam, kadar lemak dan tekstur telur asin - Faiz, Hassan; Thohari, Imam; Purwadi, Purwadi (Faculty of Animal Science, Universitas Brawijaya, 2014)
The purpose of this research were to analyze the best Curcuma xanthorrhiza juice on salted egg. The method used in this research was experimental research using completely randomized design with 4 treatments and 4 replications. The curcuma juice were divided into P0 (0%), P1 (25%), P2 (50%) and P3 (75%). The variables observed in this research were total phenol, salt content, fat content and texture. The data were analyzed by analysis of variance. The analysis was continued by Honestly Significant Difference Test if there were significant differences among variables. The results showed that the addition of curcuma juice did not significantly affect (p>0.05) the total phenol and texture. The result showed that the addition of curcuma juice gave highly significant difference (p≤0.01) on salt content and had significant difference effect (p≤0.05) on fat content. The best treatment was the addition of curcuma juice 75% which provided 0.125% of total phenol, 1.31% of salt, 36.98% of fat and 7.05 N of texture. The addition of curcuma juice could reduce the level of salt content and fat content, but did not affect the total phenol and texture. Keywords : duck egg, curcuma juice concentrate, benefits, functional food